Digitalization of land information: problems and prospects for territorial communities - Butenko, E.; Nemchenko, I. (Land Management, Cadastre and Land Monitoring, 2022)
The article substantiates the need to update the data of land cadastral information in the effective management of the land-territorial complex of communities in Ukraine. The rights and obligations of territorial communities in the use of land resources within their boundaries have been established. The legal framework is considered, on the basis of which the right to use and dispose of state-owned lands in territorial communities is formed. The problems faced by the newly formed territorial communities in the management of land resources are analyzed. Priority steps for information accessibility have been established. The actual areas of work of the land department for the digitalization of land information in territorial conditions are determined. The positive aspects of the digital possibility of territorial communities in Ukraine are highlighted. The main problems of introducing digital registers of land resources into the activities of territorial communities are identified. Prospects are considered and measures aimed at overcoming the problems of digitalization of land information are proposed. Attention is focused on the need to create a single land registry in each new community, which in turn will improve land management and increase revenues to the local budget. The relevance of introducing open registers of information on land resources of territorial communities to attract investment is substantiated. Key words: territorial community, digital ability, digitalization, land information, land asset, visualization, land accounting.